Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2020)

Les élections des écoles anglophones doivent être retardées - Garner, Linton (2020)

The QFHSA Back-to-School Survey : What Our Members Had To Say - Quebec Federation of Home and School Associations (QFHSA) (2020)
The Quebec Federation of Home and School Associations (QFHSA) surveyed its members recently on the Quebec government’s plan to reopen schools this spring. We learned that a small minority of parents (16.74%) plan to send their children back to school when it reopens. Of those who intend to keep their children at home, 65.5% are opting for distance learning; and 30%, home-schooling.

Déclaration sur l'abolition du programme « Éthique et culture religieuse » - Quebec Federation of Home and School Associations (QFHSA) (2020)

Resolution from the Board of Directors of the Quebec Federation of Home and School Associations : Challenge to Law 40 - Quebec Federation of Home and School Associations (QFHSA) (2020)

Statement on the Abolition of the "Ethics and Religious Culture" Programme - Quebec Federation of Home and School Associations (QFHSA) (2020)

Annual Report 2019-2020 : Learning in the Next Decade of Education - Leading English Education and Resource Network (LEARN) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)